Historical Dictionary of Ancient Greek Warfare - Woronoff, Jon (Rowman & Littlefield Publishers, 2002)
This resource strategically traces Greek warfare from 720 to 30 BC and its specific and extensive details-the wars, the troops, the armor, the military tactics, and other factors either affecting or affected by the wars. Read how warfare evolved during the centuries in ancient Greece from rudimentary, non-sophisticated strategies and weaponry to more complex arsenals and tactics. Includes entries on many aspects of war for which ancient Greece is historically recognized, as well as profiles of famous military and civilian leaders, including Alcibiades and Alexander the Great, who were involved in the battles on both land and sea. An extensive bibliography suggests further reading of interest. No other general work on ancient Greek warfare covers the entire period included in this volume.